ADAPTASI DAN INOVASI TEKNOLOGI PERAHU NELAYAN DAN ALAT TANGKAP TRADISIONAL DI TELUK TOMINI - Salam, Aziz; Fachrussyah, Zhulmaydin Chairil (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
The development of boat technology and traditional fishing gear, which is still predominantly used by fishing communities in Indonesia, appears to be running slowly. This study aims to determine the adaptations and technological innovations that have been applied in fishing communities for the development of capture fisheries technology in Tomini Gulf. Data and information about fishing boats and fishing gear in the form of types, functions, sizes, structures, pictures, raw materials, and changes in shape, changes in function, as well as adaptations and technological innovations that occur are obtained by field surveys conducted in fishing villages. Other data were obtained through in-depth interviews with fishermen and community leaders using interview grid instruments. Adaptations and innovations that occur in fishing boats include the use of bodi hull types on ketinting (long-tail outboard engine) boats and the use of fiberglass and PVC (Polyvinyl chloride) pipe as substitutes for wood and bamboo as raw materials for hull and outrigger buoys. The lampu suntik (waterproof lamp of LED sircuit in a used syringe plastic tube) is an innovation made on the totabito squid fishing gear. Adaptation and innovation in fisheries technology occurs part-by-part (partial) and requires proving success to gain wide acceptance. Keywords: adaptation; innovation; techology; fishing boat; fishing gear; traditional.